Enhancement in pool boiling heat transfer of ethanol and nanofluid on novel supersonic nanoblown nanofiber textured surface. Issue 4 (7th June 2022) - Thakur, Satyam Singh; Chandel, Sheshang Singh; Kakoria, Ashish; Sinha-Ray, Sumit
ABSTRACT: Pool boiling of ethanol and Cu-nanofluid was investigated on bare and novel supersonic nanoblown polymer nanofiber nanotextured copper surface. Significant improvement in early ONB (2°C reduction), CHF (23.5%), and BHTC ( 2–2.5 times) were achieved in nanotextured surface than bare one. Boiling of nanofluids led to the degradation of ONB and BHTC, with an increase in CHF by 16.7%. Synergistic effect of nanofluid boiling on nanotextured surface led to remarkable enhancement of CHF (44%), BHTC (>2.5 times), and ONB (3°C reduction). The nanofluid and nanotexture aided in ONB and CHF via enhancing nucleation sites, liquid overheating, bubble chopping, and surface wettability.